A Gravity Model for Indonesian Canned Tuna Exports to the European Union Market: An Application of PPML Estimator - Puspi Eko Wiranthi; Iwan Aminudin; Eka Rachmawati Dewi (Faculty of Economics, Universitas Sriwijaya, 2019)
In this study, we examine the determinants of Indonesian canned tuna export to the European Union (EU) market through a gravity model approach. This paper employs a gravity model approach through Poisson Pseudo-Maximum Likelihood (PPML) estimation. Data from 2006 to 2015 covering 10 countries (the Netherlands, Belgium, Italy, Germany, Poland, Portugal, Slovenia, Spain, Sweden, and the United Kingdom) were employed with HS 160414 product code specification. Constant Market Share Analysis (CMSA) was performed to examine Indonesian export growth as well as its competitors. The findings indicated that the performance of Indonesian canned tuna exports to the EU market is prominently affected by competitiveness effect while Thai canned tuna export is more affected by import growth and composition effect. The Philippines and Vietnam canned tuna exports are more affected by composition and competitiveness effect. Finally, population of the importing countries, tuna production volumes and real exchange rates significantly affect Indonesian canned tuna export to the EU.